Noninvasive analysis of skin proteins in healthy Chinese subjects using an Orbitrap Fusion Tribrid mass spectrometer. Issue 4 (18th January 2019) - Ma, Jie; Xu, Shuangjun; Wang, Xiaomeng; Zhang, Jing; Wang, Yaochi; Liu, Mengting; Jin, Ling; Wu, Mingshun; Qian, Danfeng; Li, Xueying; Zhen, Qi; Guo, Huimin; et al.
Abstract: Objective: The objective of this study was to perform noninvasive analysis of skin proteins in a healthy Chinese population using label‐free nanoflow liquid chromatography‐mass spectrometry (nLC‐MS). Materials and Methods: Five consecutive tape strippings were obtained from the volar forearm skin of healthy Chinese subjects. Proteins were extracted, and trypsin‐digested peptides were analyzed by a nanochromatography instrument coupled to an Orbitrap Fusion Tribrid mass spectrometer. Data‐dependent acquisition allowed protein identification, which was performed by using Proteome Discoverer software (v2.2). Results: In this study, we identified 80 common proteins that were expressed in the skin of healthy Chinese volunteers and divided these proteins into 16 categories, including keratins, cornified envelope proteins, and enzymes associated with substance metabolism. These proteins were closely associated with multiple functions of the skin barrier. Conclusion: This study provides a noninvasive method to analyze healthy human epidermal proteins, which are closely associated with the skin barrier. In addition, this study provides a reference for further studies on the application of proteomic technologies to investigate the role of human epidermal proteins in health and disease.